AKIBAT HUKUM TERHADAP NARAPIDANA YANG MELAKUKAN PELANGGARAN TATA TERTIB TINDAK KEKERASAN DILEMBAGA PEMASYARAKATAN KELAS II.APEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1995TENTANG PEMASYARAKATAN - Wino Thantow Malbuano; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Penitentiary is an institution of the criminal justice subsystem that has a strategic function as the implementation of imprisonment as well as a place of guidance for inmates, as written in Law Number 12 of 1995 Concerning Corrections. The imprisonment system as a criminal offender has lost its independence no longer in accordance with the level of peradap and the dignity of an independent Indonesian nation that has the philosophy of Pancasila, because the imprisonment comes from the view of individualism contained in the invaders' dictionary, which views and treats the convicted person not as a member of the community but is a member of society a public revengeThe problem that the author made the basis of this study is how the legal consequences of prisoners who commit acts of violence in prison and whether the application of sanctions against prisoners who commit violations, in accordance with the purpose of correctional measures. The purpose of this study is to determine the legal consequences of prisoners who commit acts of violence in prison and to determine the application of sanctions against prisoners who commit violations, in accordance with the purpose of correctional measures.This type of research can be classified into empirical or sociological research types, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at Penitentiary Class II A Pekanbaru City, data sources used are: primary data and secondary data, data collection techniques in this study with observation, interviews and literature review.The results of this study are first. Legal consequences given by Correctional Staff to prisoners who commit acts of violence in Class II.A Penitentiary Pekanbaru, which is to enter the exile cell for 6 (six) days and can be extended for 2 (two) times 6 (six) days and do not get the right to remission , family visit leave, conditional leave, assimilation, near-free leave, and conditional release in the current year and recorded in register F. But not all violations of the rules of violence that occur in acts are in accordance with severe disciplinary punishment, only acts of violence that cause injuries physical punishment given severe disciplinary, second, the application of sanctions against inmates who violate the rules of violence is not in accordance with the purpose of correctional due to the many inhibiting factors in its implementation, as for the inhibiting factor is the lack of personnel security officers Class II.A Pekanbaru Penitentiary, incomplete facilities and infrastructure of Class II.A Penitentiary, Pekanbaru, over capacity, and many guests visiting Class II.A Penitentiary Pekanbaru.Keywords: Prisoners, Penitentiary